Microelectromechanical accelerometer under mechanical impact conditions; Control and Communications (SIBCON) - Nesterenko T. G. Tamara Georgievna; Barbin E. S. Evgeny Sergeevich; Koleda A. N. Aleksey Nikolaevich; Zorina E. V. Elena Vasiljevna (2016, 2016)
Title screen